About Not Countable Ideals in a Semi-Lattice of the Enumeration Degrees - B. I. Solon; V. V. Tikhov (Моделирование и анализ информационных систем, 2012)
This paper is dedicated to the study of ideals in semi-lattice of the enumeration degrees.